First Italian validation of the “Satisfaction with simulation experience” scale (SSE) for the evaluation of the learning experience through simulation. - Guasconi, Massimo; Tansini, Beatrice; Granata, Carlotta; Beretta, Maurizio; Bertuol, Maria; Lucenti, Enrico; Deiana, Laura; Artioli, Giovanna; Sarli, Leopoldo (Acta Biomedica Atenei Parmensis, 2021)
Background and aim of the work. Training in simulation through "mannequins" is increasingly widespread among nursing students. In the Italian context, however, there are no tools that measure the degree of student satisfaction after clinical training through simulation. The aim of the study is to provide a first validation in Italian of the Satisfaction with simulation experience” (SSE) scale, a tool already validated in several languages. Methods. After obtaining the author’s consent, the SSE was subjected to forward and backward translation. The content validity was assessed by 5 training experts by calculating the Content Validity Index by Item and by Scale (I-CVI and S-CVI); the face validity was tested on 4 nursing students who had participated in a simulation experience. Subsequently, the SSE was administered to 10 nursing students with test-retest after 7 days in order to evaluate the reliability by calculating the reliability coefficient (r) and Cronbach’s α. Results. The author approved the final version of the SSE translated into Italian: I-CVI values>0.80 and S-CVI was 0.94. r is 0.88 and the α of the scale is 0.713. Conclusions. The detected values of I-CVI and S-CVI are satisfactory, demonstrating the validity of the content of the SSE-ITA. The test-retest showed "optimal" reliability and the α was considered acceptable given the little deviation from the original (0.776). Although the results demonstrate satisfactory values, this is a first validation and other studies with larger samples are needed.